Interwoven Temporalities: Reading Madeleine Thien’s Dogs at the Perimeter - Beauregard, Guy (Studies in Canadian Literature, 2014)
This paper focuses on Madeleine Thien’s novel Dogs at the Perimeter (2011), a text that tells the stories of various characters whose lives have in distinct ways been shaped by the Khmer Rouge regime in Cambodia (1975-1979), a time in which an estimated 1.7 to 2 million people were killed or died as a result of state action. It engages with the politics of the knowledge that has been produced around this text to suggest that the challenges critics have faced while encountering the novel’s complex interwoven temporalities could provide an opportunity to engage with the limits of our various situated reading practices. It argues that Gayatri Chakravorty Spivak’s injunction to “go beyond the self-identity of nationalism towards the complex textuality of the international” may help guide us in learning to read representations of difficult histories across the North-South divide.